Filosofi Membelah Anak Panah: Memahami Kehidupan - Saragi, Oliver Richardo; Muhammad Fikriansah; Hasugian, Lewi Ebenezer (AGUSPATI RESEARCH INSTITUTA, 2024)
The aim of this study is to present a critical review of the book titled